TRANSPARANSI DALAM PENGELOLAAN ALOKASI DANA DESA (STUDI DI DESA MINTIN, KECAMATAN KAHAYAN HILIR, KABUPATEN PULANG PISAU) - MARLENDIE; Anyualatha Haridison (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Palangka Raya, 2017)
This study focuses attention on the Openness of the Revenue and Expenditure Budget of the Village from Planning, Implementation, to Accountability with the aim of describing Transparency of Village Fund Allocation Management. This research is conducted because the Implementation Team of the allocation of village funds is considered less in terms of capacity and capability. This research is expected to be useful for District Government of PulangPisau, especially Kahayan Hilir Sub-district of Mintin Village in an effort to increase Transparency of Village Fund Allocation Management This research was conducted at Mintin Village Office, Kahayan Hilir Sub-district, PulangPisau District. As the selected informants are the Village Head, Village Secretary, Village Kaur and RT who are considered to represent the community in the research unit in the management of the Village Fund Allocation. The study was conducted with in-depth interviews and by direct observation of the implementation Allocation of village funds. The results of this study indicate that for the planning and implementation of Village Fund Allocation activities, it already shows the existence of transparent management. While in the accountability seen by physical results have shown a transparent implementation, from the administration side there is no need for further coaching, because it is fully in accordance with the provisions. Transparency in the Planning of APBDes Desa Mintin which is run by the Village Government apparatus refers to the regulation applied through the Law and Government Regulation and Regent Regulation obtained through various training with technical guidance followed by the Village Government apparatus.